2018
DOI: 10.1016/j.cell.2018.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight Brightens Learning and Memory

Abstract: Sunlight can alter mood, behavior, and cognition, but the cellular basis of this phenomenon remains to be fully elucidated. In this issue of Cell, Zhu et al. shed light on a UV-dependent metabolic pathway that leads to increased synaptic release of glutamate and enhanced motor learning and memory in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…[40] It has been reported that exposure to light improves brain responses to cognitive tasks, and short-and long-term plasticity. [41,42] To mimic the memory consolidation effect of biological synapse, we illuminated 1 mW cm -2 of polychromatic light on the DGOST-DREGE device (Figure S11, Supporting Information). Light-induced postsynaptic signal enhancement and charge retention were clearly observed from the DGOST-DREGE device, indicating that our device behaves similarly to an actual synapse.…”
Section: Resultsmentioning
confidence: 99%
“…[40] It has been reported that exposure to light improves brain responses to cognitive tasks, and short-and long-term plasticity. [41,42] To mimic the memory consolidation effect of biological synapse, we illuminated 1 mW cm -2 of polychromatic light on the DGOST-DREGE device (Figure S11, Supporting Information). Light-induced postsynaptic signal enhancement and charge retention were clearly observed from the DGOST-DREGE device, indicating that our device behaves similarly to an actual synapse.…”
Section: Resultsmentioning
confidence: 99%
“…In PD, an in vivo study has shown that chronic unregulated cytosolic dopamine alone is enough to cause neurodegeneration [ 196 ]. Glutamate is an excitatory neurotransmitter implicated in the regulation of neurogenesis, synaptogenesis, memory, and neuronal plasticity [ 197 , 198 , 199 , 200 ]. This is especially true of the action of glutamate at synaptic NMDARs; however, glutamate activity at extrasynaptic NMDARs can lead to neurotoxicity and cell death [ 201 , 202 , 203 ].…”
Section: Leveraging Gefb and Ipsc Technologies For Pre-clinical Appli...mentioning
confidence: 99%
“…Glutamate is the predominant excitatory neurotransmitter in the brain ( Curtis and Johnston, 1974 ; Fonnum, 1984 ) and is critical to numerous central nervous system (CNS) functions ( Tang et al, 1999 ; Matsuzaki et al, 2004 ; Chantranupong and Sabatini, 2018 ; Boender et al, 2020 ; Stephenson-Jones et al, 2020 ). Anomalously elevated glutamate in the synapse results in CNS neurotoxicity; removal of glutamate occurs via glutamate transporters (excitatory amino acid transporters; EAATs), as enzymes that metabolize glutamate in the synaptic cleft are scarce.…”
Section: Introductionmentioning
confidence: 99%